2003
DOI: 10.1038/sj.ijir.3901006
|View full text |Cite
|
Sign up to set email alerts
|

Structured interview on erectile dysfunction (SIEDY©): a new, multidimensional instrument for quantification of pathogenetic issues on erectile dysfunction

Abstract: The aim of the present study is the definition of a brief structured interview (SI) providing scores useful for identification and quantification of pathogenetic factors of erectile dysfunction (ED). A SI was developed and applied to a consecutive series of 320 ED patients. A 13-item SI, with threefactor analysis-derived scales, was identified and applied for validation to an independent consecutive series of 194 ED patients. PGE 1 (10 lg) intracavernosal injection, penile duplex ultrasound (PDU), blood hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
382
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(387 citation statements)
references
References 25 publications
3
382
1
1
Order By: Relevance
“…We found that patients with difficulties in achieving a valid erection (sample B) showed a higher prevalence of organic conditions related to ED, when compared with those complaining difficulties in maintaining erection (sample A), as confirmed by higher scores on the SIEDY r scale 1 which explores the organic component of ED. 5 The greater involvement of organic factors in patients with difficulties in obtaining rather than maintaining erection was further confirmed by results of FIC, NPT, and PDU tests. Our findings support the previously unproved hypothesis, that patients experiencing difficulties in maintaining erection could recognize a more psychogenic, rather than organic, pathogenesis.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…We found that patients with difficulties in achieving a valid erection (sample B) showed a higher prevalence of organic conditions related to ED, when compared with those complaining difficulties in maintaining erection (sample A), as confirmed by higher scores on the SIEDY r scale 1 which explores the organic component of ED. 5 The greater involvement of organic factors in patients with difficulties in obtaining rather than maintaining erection was further confirmed by results of FIC, NPT, and PDU tests. Our findings support the previously unproved hypothesis, that patients experiencing difficulties in maintaining erection could recognize a more psychogenic, rather than organic, pathogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…7 Patients were asked to specify any current pharmacological treatment; drugs listed in Boderick and Foremann, 8 were considered capable of interfering with sexual function. Considering NIH definition of impotence 1 and using SIEDY r appendix A, 5 we identified two groups of patients: sample A, (difficulties in maintaining, rather than achieving, an erection) and sample B (with main problems in achieving an erection) ( Table 1). Sample A is composed of patients who reported erection not valid enough for penetration in less than 25% of cases and difficulties in maintaining erection in over 25% of the occasions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations